2018
DOI: 10.1007/s10802-018-0469-8
|View full text |Cite
|
Sign up to set email alerts
|

A Phenotype of Childhood Autism Is Associated with Preexisting Maternal Anxiety and Depression

Abstract: This study explored whether ASD phenotypes in the child were associated with a history of anxiety or depression in the mother. We hypothesized that an ASD profile in children characterized by mild delays and increased rates of dysregulation would be associated with preexisting maternal anxiety or depression. Participants were 672 preschool children with ASD and their mothers. Children were classified as ASD after a comprehensive developmental evaluation. Mothers reported whether a healthcare provider ever diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
(88 reference statements)
0
17
0
1
Order By: Relevance
“…The lack of parents' history of psychiatric disorders is another limitation of this study. This information is important not only to increase comprehension of PC in ASD children Wiggins et al ( 119 ), but also to accurately interpreting parent–report. For example, the possible negative bias of anxious or depressed parents can lead them to overestimate the amount of symptoms of their own kid ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of parents' history of psychiatric disorders is another limitation of this study. This information is important not only to increase comprehension of PC in ASD children Wiggins et al ( 119 ), but also to accurately interpreting parent–report. For example, the possible negative bias of anxious or depressed parents can lead them to overestimate the amount of symptoms of their own kid ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…RCT compared children with anxiety with ASD and those without ASD. It is known that these two cohorts share phenotypes, similar developmental, behavioural, and cognitive profiles ( Wiggins et al, 2019 ) which overlap and could have confounded results in the study, this observation recommended further studies to compare alliance in ASD with other disorders ( Klebanoff et al, 2019 ). Statistical significance was possibly compromised by small sample size and it was an issue in the trials by way of introducing sampling bias leading to the reduced power of studies ( Anderson et al, 2012 ; Levin et al, 2012 ; Chu et al, 2014 ; McLeod et al, 2014 ; Labouliere et al, 2017 ; Zorzella et al, 2017 ; Carpenter et al, 2018 ; Kirsch et al, 2018 ; Albaum et al, 2020 ; Loos et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showing an association between maternal postnatal depressive symptoms and childhood ASD are less robust and need to be interpreted with caution. Although some prior studies have reported an association between antenatal maternal depression and offspring’s ASD, 10,43 and postnatal depression has been suggested as a potential focus of cross-domain studies of ASD, 44 there is no clear aetiological role of maternal postnatal depression in the development of ASD per se . Also, given that mothers with ASD are more likely to suffer from perinatal depression than mothers without ASD, 45 and ASD is highly heritable, 46 maternal depression may be a confounder in our observed results.…”
Section: Discussionmentioning
confidence: 98%